Factors related to self-rated health in teleworkers raising children: focusing on gender differences - Motoko Ohira; Yoko Ichikawa; Madoka Tsuji; Tomoyuki Hasegawa; Shin Saito (Environmental and Occupational Health Practice)
Objectives: Teleworking is a flexible means of working to effectively utilize one’s time and workplace using information and communication technology. However, teleworking can also lead to work–life conflict and health problems. To support the health of teleworkers, this study aimed to elucidate the factors correlated with the self-rated health of teleworkers raising children, focusing on differences between genders. Methods: The study sample included 1,000 teleworkers (500 women and 500 men). Results: The responses to questionnaire items about health differed between men and women. For men, “marital status,” “walks and exercises,” “keeps an uplifted state of mind as much as possible,” and “work-to-family negative spillover” were extracted. For women, “leads a disciplined life,” “keeps an uplifted state of mind as much as possible,” “eating speed compared with others: slower,” and “sufficiently rests through sleep” were found to affect self-rated health. Conclusions: For male teleworkers raising children, sufficient exercise and physical activity is a crucial aspect of health management. For female teleworkers raising children, self-discipline is needed.